SEM/EDS Analysis of Tubules and Mineral Deposition in the Dentin of Children with Osteogenesis Imperfecta - Martín-Vacas, Andrea; Vera-González, Vicente; Ramírez-Castellanos, Julio; González-Gil, Diego; de Nova García, Manuel Joaquín (Applied sciences, 2023)
The aim is to quantitatively analyze the diameter and tubular density and semi-quantitatively analyze the elemental composition (Calcium and Phosphorus) in the dentin of primary teeth of children with Osteogenesis Imperfecta (OI) in comparison with a control group. Material and methods: A microstructural (in vitro) analysis of primary teeth of children with OI was performed with SEM and EDS. The variables measured were the tubule count (tubule/mm2) and diameter (µm) at 2000 times magnification at four points of the dentin of different depths. A semiquantitative analysis of the elemental composition of the dentin was performed with EDS of Calcium and Phosphorus (cps). Descriptive and inferential analysis (Fisher’s exact test, the Mann–Whitney U test, the Kruskal–Wallis test, the Bonferroni post hoc test, the ANOVA test of repeated measures, a test of inter- and intra-subject effects, and the Geisser–Greenhouse test) were carried out. Data were analyzed with a 95% confidence level (p-value < 0.05). Results: A total of 25 deciduous teeth from 17 patients with OI and 30 teeth from healthy children were studied. There were differences in the count and tubular diameter for the control group with OI; in addition, the behavior curve changed when the systemic disease was severe. While there were no differences in the amount of dentinal Calcium, the OI tooth showed a significantly lower amount of Phosphorus (p < 0.05), except in the pulpal dentin (p > 0.05). Conclusion: The alterations of the dentinal tubules (density and diameter) were more pronounced in the most severe phenotypes of systemic disease. The amount of Phosphorus was decreased in the dentin of the primary teeth of children with OI compared to the control group.